A mixed acid methodology to produce thermally stable cellulose nanocrystal at high yield using phosphoric acid - Khairatun Najwa, Mohd Amin; Hosseinmardi, Alireza; Martin, Darren J.; Annamalai, Pratheep K. (KeAi Communications Co., 2022)
Cellulose nanocrystal (CNC) with distinctive shape-morphology, enhanced thermal stability and dispersibility is essential for overcoming the challenges in processing polymer/CNC nanocomposites through melt compounding at elevated temperatures. This study shows a mixed acid hydrolysis method to produce CNC with improved thermal stability and high productivity. The use of phosphoric acid (H3PO4), as a mild acid, in combination with a strong acid either sulphuric acid (H2SO4) or hydrochloric acid (HCl) leads to reduced use of strong acids and low impact on our environment. The influences of acid combination and sequence of addition on the production yield were investigated by retaining the proportion of H3PO4 to corrosive acid (H2SO4 and HCl) 4 to 1, and solid to liquid ratio 1꞉75. This methodology has enabled to isolate CNC with higher thermal stability, dispersibility and productivity in terms of amount acid used 1 g of CNC, as compared with single acid hydrolysis. The CNC produced using the combination of H3PO4 and HCl exhibits high thermal stability, dispersibility and rod-like shape morphology with length and width of (424 ± 86) and (22 ± 3) nm, respectively. Moreover, this approach has reduced H3PO4 consumption by 54% as compared with single acid hydrolysis method for the production of same amount of CNC.